Self-Reported Dental Caries by Mexican Elementary and Middle-School Schoolchildren in the Context of Socioeconomic Indicators: A National Ecological Study - Juan Fernando Casanova-Rosado; Alejandro José Casanova-Rosado; Mirna Minaya-Sánchez; Juan Alejandro Casanova-Sarmiento; José Luis Robles-Minaya; Sonia Márquez-Rodríguez; Mariana Mora-Acosta; Rosalina Islas-Zarazúa; María de Lourdes Márquez-Corona; Leticia Ávila-Burgos; Carlo Eduardo Medina-Solís; Gerardo Maupomé (MDPI AG, 2021)
The objective of the present research was to quantify the association between dental caries self-report and socioeconomic indicators in Mexican children. An ecological study included a self-report of dental caries in schoolchildren enrolled in public elementary and middle schools derived from the National School Health Survey. A total of 73,560 schoolchildren (representing 19,745,366 students) aged 5 to 16 years were included. Socioeconomic variables included were scales depicting physical characteristics of housing, purchasing power, etc. used in national surveys in Mexico to measure deprivation, poverty, and income inequality in official data. Data were analyzed in Stata using Spearman's correlation test. For the most part, no association (p > 0.05) was found between caries self-report, socioeconomic variables, or the Gini index. However, caries self-report in elementary schoolchildren and total (elementary + middle-school) schoolchildren groups was positively correlated (p < 0.05) with two poverty variables: extreme poverty by income (value of personal food purchases per month) and poverty by income (value of personal food and non-food purchases per month). National data for dental caries self-report were associated-at the ecological level-with a few socioeconomic indicators but not with most of the usual and customary indicators used in national surveys in Mexico.